Addition of Carbon Sources to Pineapple Waste Media in the Production of Single Cell Protein Biomass Saccharomyces cerevisiae - Nurmalasari, Anggi; Maharani, Shinta (Jurnal Riset Biologi dan Aplikasinya, 2020)
Single-cell protein (SCP) is the term used for crude or pure protein derived from simple single or multi-celled microorganisms. Pineapple peel contains monosaccharides as much as 10.8% so that it can be used as a fermentation medium in single-cell protein production. The purpose of this study was to determine the effect of adding carbon sources of fructose and sucrose on pH, cell dry weight, and protein content in the manufacture of single-cell proteins. This study used a completely randomized design (CRD) with two factors, namely the addition of carbon (fructose, sucrose, and control) and fermentation time (24.48, and 72 hours). The data analysis used the variance test and the Duncan Multiple Range Test (DMRT) continued to test with a confidence level of 95%. The results showed that the addition of carbon to the media had a very significant effect on media pH, cell dry weight, and protein content. In the medium with the addition of fructose it has a pH of 3.81; dry weight 0.4203 grams; and protein content 69.08/L. Whereas in the media with the addition of sucrose, the pH was 4.33, the dry weight of the cells was 0.3385 grams, and the cells had a protein content of 85.55 mg/L. The addition of a fructose carbon source gave the cell dry weight more than the addition of carbon sucrose